Hydrothermal controllable synthesis of hollow carbon particles: Reaction-growth mechanism. (2nd November 2020) - Li, Yingjiao; Shi, Qin; Luo, Yong; Chu, Guangwen; Zou, Haikui; Zhang, Liangliang; Sun, Baochang
Highlights: This work provided a novel route for synthesis carbon with different morphologies. Different operating conditions can impact the characteristics of carbon particles. The reaction and growth mechanism of the hollow carbon particles were exposed. We proposed the mother liquor and particle analysis method to study these mechanism. The hollow vase-like carbon particles was adopted to adsorb and degrade the phenol. Abstract: In this work, the reaction and growth mechanism of carbon particles synthesized via hydrothermal method have been studied. The reaction mechanism of d -glucose – d -ribose – Furanic group – Arene group (DDFA) and growth mechanism of P123 – Sphere micelle – Hollow carbon sphere – Hollow vase-like carbon particle (PSHH) were proposed. It was found that the morphology, average particle size and particle size distribution of carbon particles can be varied by regulating operating conditions. In addition, the prepared hollow vase-like carbon particle (HVCP) was adopted as an adsorbent and for preparing catalyst. The results showed that the HVCP adsorption capacity is 4.5 times higher than commercial activated carbon (CAC) for phenol adsorption, and could great enhance the photocatalytic degradation of phenol. This work may provide guidance for controllable synthesis of carbonaceous materials and research method for the related reaction and growth mechanism.